Evaluating the Immediate Response of Country-Wide Health Systems to the Covid-19 Pandemic: Applying the Gray Incidence Analysis Model - Qazi, Tehmina Fiaz; Shaukat, Muhammad Zeeshan; Niazi, Abdul Aziz Khan; Basit, Abdul (Frontiers in Public Health, 2021)
Purpose of the study is to evaluate county-wide health systems using the data set of first wave of COVID-19 pandemic. Overall design of study comprises of literature review, secondary data and mathematical analysis. It is a cross sectional quantitative study following deductive approach. It uses the data of first wave of COVID-19 pandemic taken from the website of Worldometer as on April 8, 2020. The study uses grey incidence analysis model (commonly known as Grey Relational Analysis i.e. GRA) as research methodology. On bases of the results of GRA a classification has been made under a predetermined scheme of ensigns like: much better, better, somewhat better, fair, poor, somewhat worse and worse health system. There are total 211 countries that have been divided in to seven aforementioned categories. Findings of the study show that majorly, Southern Africa Development Community (SADC) countries fall under much better ensign, whereas, Organization for Economic Co-operation and Development (OECD), Schengen Area (SA) and/or European Union (EU) countries fall under worse ensign. Pakistan fall under the ensign of poor. It is an original attempt to evaluate response of health systems based on real data using a scientific methodology. The study provides valuable information about health systems of the countries for forming informed opinion about health systems thereof. The study provides useful new information to stakeholders and new framework to the future researches.